1982
DOI: 10.1007/bf00002502
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of mercuric chloride and methylmercuric chloride to Fundulus heteroclitus embryos in relation to exposure conditions

Abstract: SynopsisEmbryos in specific stage of the estuarine teleost, Fundulus heteroclitus, were exposed to mercuric chloride (MC) and methylmercuric chloride (MMC) under several distinct treatment conditions. Four-eight cell stage eggs (O-day old) were exposed for 4 days (continuous), 2 days and one day to each mercury compound. Oneday old (mid-blastula), 2-day old (mid-neurula) and 5-day old (beating heart) embryos were exposed 4 days to MC and MMC. Mortality for the four days immediately following the initiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Besides the fact that the earliest stages of cell division are the most sensitive to Hg toxicity in the fish embryonic period, methylmercury is more toxic than InorgHg in this situation (Sharp & Neff, 1982). In the present study, we found higher OrgHg concentrations than InorgHg in the gonads.…”
Section: Discussionsupporting
confidence: 64%
“…Besides the fact that the earliest stages of cell division are the most sensitive to Hg toxicity in the fish embryonic period, methylmercury is more toxic than InorgHg in this situation (Sharp & Neff, 1982). In the present study, we found higher OrgHg concentrations than InorgHg in the gonads.…”
Section: Discussionsupporting
confidence: 64%
“…Hatching success was decreased in embryos exposed to 15 μg/L, with no hatching occurring at higher concentrations. Short‐term (1‐ to 5‐d) exposure of mummichog embryos to higher concentrations of inorganic mercury (40 μg/L) and methylmercury (30 μg/L) decreased survival, whereas a subchronic (32‐d) exposure to 10 μg/L decreased hatching success [119,120]. Embryos of the mummichog exposed to 5 μg/L of methylmercury until 3 d posthatch demonstrated no change in their morphology yet exhibited impairment in the ability of larvae to capture prey [121].…”
Section: Disruption Of Female Reproductive Functionmentioning
confidence: 99%
“…The present study showed that the 48-h LC 50 value of MeHg (28.39 µg L −1 ) to embryos of large yellow croaker was generally lower than fathead minnow (Pimephales promelas, 71 µg L −1 ; Devlin, 2006), killifish (Fundulus heteroclitus, 50 µg L −1 ; Sharp and Neff, 1982), zebrafish (Danio rerio, 90 µg L −1 ; Cambero and Calvo, 2010) and coho salmon (Oncorhynchus kisutch, 54-71 µg L −1 ; Devlin and Mottet, 1992), but higher than the Japanese flounder (Paralichthys olivaceus, 15.3 µg L −1 ; Ren et al, 2019). While the 48-h LC 50 (18.27 µg L −1 ) and 96-h LC 50 (9.28 µg L −1 ) values of MeHg to large yellow croaker larvae was much Frontiers in Marine Science | www.frontiersin.org ;Wobeser, 1975;Mozhdeganloo et al, 2015), blue gourami (Trichogaster trichopterus, 48-h LC 50 , 94 µg L −1 , 96h LC 50 , 89 µg L −1 ; Roales and Perlmutter, 1974) and Japanese flounder (48-h LC 50 , 20.7 µg L −1 , 96-h LC 50 , 16.3 µg L −1 ).…”
Section: Acute Toxicity Of Mehg To Embryos and Larvaementioning
confidence: 49%
“…Additionally, the chorions during late embryogenesis will gradually break and thereby increase the susceptibility of the embryos to waterborne toxicants (Ren et al, 2019). Therefore, the sensitivity of embryos to toxicants could be related to the processes by which the chorions biologically function in response to the waterborne toxicants entering the embryos (Sharp and Neff, 1982).…”
Section: Acute Toxicity Of Mehg To Embryos and Larvaementioning
confidence: 99%